Evidence from Supervisory Measures for Bank Lending and Npls Control During COVID 19 Crisis - Cerrone, Rosaria (Archives of Business Research, 2021)
The highest impact of Covid-19 crisis on banks is related to their loan portfolios where many borrowers are facing sharp collapse in their income, and difficulty in repaying their obligations. Regulatory and supervisory authorities have issued statements or guidelines to banks on how to deal with the impact of the outbreak, including relation to easing loan terms and conditions for impacted borrowers. This paper aims to provide some policy views on the appropriate response to Covid-19. Supervisors and regulators should play an integral part contributing to public policy responses to the pandemic. Consistent with their mandate of ensuring safety and soundness, supervisors’ action requires a balancing act where banks are encouraged to restructure loans and use the flexibility embedded in the prudential framework by financing viable firms. This paper presents the state of arts and some considerations about the future banks’ conditions facing NPLs increase and their earnings reduction.